Žmonių sauga Lietuvos statybose - Čyras, Petras; Jaras, Arūnas (Journal of Civil Engineering and Management, 1996)
Occupational safety on construction sites of LithuaniaSocial instability, violation of human rights to work have made the conditions of safe and harmless work worse. 19 mortal, 42 serious and 796 slight accidents occurred on construction sites during 1995 in Lithuania. The main reasons of occupational accidents are violation of work discipline and lack of organization. 24 708 days are lost because of occupational injuries, or in other words 96 builders did not work for the whole year, and 528.9 thousand litas was paid out according to the lists of disablement. The bad state in occupational safety is unprofitable.Besides, old norms and regulations are still valid at the present time, and hundreds of them are approved as far back as 1980. The drawing up of new regulations is just taking place in Lithuania.The compensation system being in force for employees, who work under harmful and hazardous conditions and social security system for those, who had suffered injuries and occupational diseases, do not stimulate employers to create healthy and safe working conditions.The factor of rest can be observed on construction sites. The heads of construction sites entrust the workers themselves to organize the work without the projects of work execution. Instructions on occupational safety and fire protection are just formal. Many of employees work without the employment contracts.Employers start to understand already that it's better to have labour protection service instead of paying fines for violation of labour protection regulations. The intellect and exacting every-day control of labour protection service specialist brings much more benefit for the prevention of occupational accidents than seldom visits of State Labour Inspection inspector to the enterprise or construction sites.The state of occupational safety depends on psychological factors, too. These factors can be grouped into three groups:• natural of the human—natural inborn dispositions (the nervous system, memory, attention, the speed of reaction, intellect);• psychological peculiarities of personality (the features of human professional activities, leadership, erudition);• professional knowledge formed during learning, studying and training.The human psychology determines how the person interprets and copes with the things going on around him and related to him. Two different persons will act differently in the same situation. When a person reacts sensitively to weak and insignificant signals, he will pay attention to preparative and preventive work, think about potential danger and will take care to avoid accident. And vice versa, people who are not sensitive for such signals takes too little care to insure against accidents. It is reasonable to test psychologically an employee before signing an employment contract with him under market circumstances. It will be one of the conditions fulfilled for professional selection, which will decrease expenses for further training and professional activity of an employee.Fatal and serious disasters on construction sites decreased twice in 1995 as compared to 1994. And the total number of accidents decreased by 12 cases only (Table 1). Dynamics of mortal, heavy and slight accidents in 1991–95 is depicted in Fig. 1.The usage of alcohol is closely related to psycho-emotional stress. It has an influence on the accidents, too. 8 employees were killed while being drunk in 1995. It is 42.11% of total number of killed employees.The most dangerous occupations on construction sites are those of auxiliary workers, bricklayers, carpenters, welders and concreters.Majority of accidents happen to the persons who work for less than one year (fatal accidents – 8, heavy accidents –16, slight accidents –163, or 44.44%, 41.08%, 32.21%, respectively).Article in Lithuanian.First Published Online: 26 Jul 2012